2020
DOI: 10.1002/ncp.10591
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Outcomes of Enteral Nutrition in Extracorporeal Membrane Oxygenation

Abstract: Extracorporeal membrane oxygenation (ECMO) is a supportive care system for patients with respiratory or cardiac failure. Patients requiring ECMO are at risk for significant inflammation, prolonged hospitalization, and acquired malnutrition and sarcopenia. Societal guidelines recommend early enteral nutrition in critically ill patients; however, in this population, optimal timing and dose of nutrition remains unknown and fear of reduced splanchnic perfusion, delayed gastric emptying, and bowel ischemia poses a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
0
22
0
3
Order By: Relevance
“…In addition, based on the result that more than 90% of patients in the MCS group can continue EN, the use of MCS itself is unlikely to be a risk factor for the occurrence of complications, increased LoS in the CCU, and mortality. Since there have been many beneficial reports of early EN for critically ill patients [1,4e6], and EN during MCS appears to be safe, tolerated, and associated with improved outcomes in multiple other studies [26,27], early EN initiation in patients with severe AHF on MCS is recommended if they are hemodynamically stable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, based on the result that more than 90% of patients in the MCS group can continue EN, the use of MCS itself is unlikely to be a risk factor for the occurrence of complications, increased LoS in the CCU, and mortality. Since there have been many beneficial reports of early EN for critically ill patients [1,4e6], and EN during MCS appears to be safe, tolerated, and associated with improved outcomes in multiple other studies [26,27], early EN initiation in patients with severe AHF on MCS is recommended if they are hemodynamically stable.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the challenges associated with ECMO support that have been documented include delayed gastric emptying and higher risk for enteric ischemia [ 14 •]. Observational literature has shown that patients on ECMO tolerate gastric EN safely [ 2 , 56 , 57 ]. A study by Obhe et al, found that compared to delayed EN, early EN within 2 days of initiating ECMO had a decrease in 28-day mortality, and there were no incidences of enteric ischemia [ 58 ].…”
Section: Special Populationsmentioning
confidence: 99%
“…In a second study by Park et al, there was a decrease in 90-day mortality with increased EN energy and protein delivery [ 59 ]. While the literature is sparce with regards to nutrition in COVID patients requiring ECMO support, extrapolation of the existing literature on critically ill patient’s requiring ECMO suggests that early EN is safe and tolerated [ 57 ]. The recommendation for nutritional therapy during ECMO includes early initiation of EN at trophic dose with slow advancement over the first week of critical illness [ 2 ].…”
Section: Special Populationsmentioning
confidence: 99%
“…Moreover, this MNT strategy might also be beneficial to attenuate muscle wasting and ICUacquired weakness. 11,40,41 On the contrary, early EN may be associated with an increased risk of feeding intolerance, which includes nausea and vomiting with pulmonary aspiration, pneumonia, and-in the context of high-dose vasopressors-nonocclusive mesenteric ischemia and bowel necrosis. 8,42,43 Patients receiving ECMO may require frequent procedures leading to EN interruptions, 13 which may contribute to macronutrient and micronutrient deficiencies.…”
Section: The Role Of En In Patients Receiving Ecmomentioning
confidence: 99%
“…Furthermore, the often underrecognized risk of underfeeding may be reduced, as the target caloric goal is reached faster compared with a late strategy. Moreover, this MNT strategy might also be beneficial to attenuate muscle wasting and ICU‐acquired weakness 11,40,41 . On the contrary, early EN may be associated with an increased risk of feeding intolerance, which includes nausea and vomiting with pulmonary aspiration, pneumonia, and—in the context of high‐dose vasopressors—nonocclusive mesenteric ischemia and bowel necrosis 8,42,43 .…”
Section: Guidance On Timing and Route Of Mntmentioning
confidence: 99%